2014
DOI: 10.1002/ana.24165
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet B light attenuates the systemic immune response in central nervous system autoimmunity

Abstract: Local UVB radiation of the skin influences systemic immune reactions and attenuates systemic autoimmunity via the induction of skin-derived tolerogenic DCs and Tregs. Our data could have implications for the understanding or therapeutic modulation of environmental factors that influence immune tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(100 citation statements)
references
References 47 publications
2
95
2
1
Order By: Relevance
“…Moreover, a statistically significant improvement in the scores EDSS, IPSS and BARS were detected; on the other hand the scores of MAS did not change significantly. In agreement with our results, several studies have reported significant improvement in the EDSS of RRMS patients after either broad band UVB phototherapy as our study (Essa et al, 2016) or narrow band UVB phototherapy ( for 5times/week for 6 weeks) (Breuer et al,2014).…”
Section: Discussion:-supporting
confidence: 93%
“…Moreover, a statistically significant improvement in the scores EDSS, IPSS and BARS were detected; on the other hand the scores of MAS did not change significantly. In agreement with our results, several studies have reported significant improvement in the EDSS of RRMS patients after either broad band UVB phototherapy as our study (Essa et al, 2016) or narrow band UVB phototherapy ( for 5times/week for 6 weeks) (Breuer et al,2014).…”
Section: Discussion:-supporting
confidence: 93%
“…PCR has been performed as described previously (Breuer et al, 2014). In short, RNA was extracted from primary human brain microvascular endothelial cells using TRIzol reagent (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…A retrospective data analysis conducted in France showed an association between regional variation in MS prevalence and UVB radiation (Orton et al, 2011). While UVB radiation is also thought to have a VD independent immunomodulatory effect (Breuer et al, 2014), it contributes to approximately 90% of the body's 25(OH) D supply (Federal Office for Radiation Protection (Germany), 2012).…”
Section: Introductionmentioning
confidence: 99%